The "universal" in UHC and Ghana's National Health Insurance Scheme: Policy and implementation challenges and dilemmas of a lower middle income country - Agyepong, I.A.; Abankwah, D.N.Y.; Abroso, A.; Chun, C.; Dodoo, J.N.O.; Lee, S.; Mensah, S.A.; Musah, M.; Twum, A.; Oh, J.; Park, J.; Yang, D.; et al. (BioMed Central Ltd., 2016)
Background: Unsafe abortion is an issue of public health concern and contributes significantly to maternal morbidity and mortality globally. Abortion evokes religious, moral, ethical, socio-cultural and medical concerns which mean it is highly stigmatized and this poses a threat to both providers and researchers. This study sought to explore challenges to providing safe abortion services from the perspective of health providers in Ghana. Methods: A descriptive qualitative study using in-depth interviews was conducted. The study was conducted in three (3) hospitals and five (5) health centres in the capital city in Ghana. Participants (n = 36) consisted of obstetrician/gynaecologists, nurse-midwives and pharmacists. Results: Stigma affects provision of safe-abortion services in Ghana in a number of ways. The ambiguities in Ghanaian abortion law and lack of overt institutional support for practitioners increased reluctance to openly provide for fear of stigmatisation and legal threat. Negative provider attitudes that stigmatised women seeking abortion care were frequently driven by socio-cultural and religious norms that highly stigmatise abortion practice. Exposure to higher levels of education, including training overseas, seemed to result in more positive, less stigmatising views towards the need for safe abortion services. Nevertheless, physicians open to practicing abortion were still very concerned about stigma by association. Conclusions: Stigma constitutes an overarching impediment for abortion service provision. It affects health providers providing such services and even researchers who study the subject. Exposure to wider debate and education seem to influence attitudes and values clarification training may prove useful. Proper dissemination of existing guidelines and overt institutional support for provision of safe services also needs to be rolled out.
Keywords: Abortion; Ghana; Qualitative research; Skilled providers; Stigma